Method Implementation Zikir Tarekat Qadiriyah Wa Naqsyabandiyah In Fostering Student Piety - Jamil, Riad; Trisnamansyah, Sutaryat; Hanafiah, Hanafiah; Karim Fatkhullah, Faiz (CV. Inara, 2022)
This research is motivated by the implementation of TQN remembrance coaching in fostering student piety, due to the lack of student piety coaching through the remembrance method in schools or madrasas providing education. schools and madrasas. The purpose of this study is to find out how the implementation of TQN remembrance in fostering student piety in two schools that provide general education and religious education in finding actual profiles through a management theory approach. Specifically, this study describes and analyzes (1) Planning, (2) Implementation, (3) Evaluation and (4) Follow-up on the development of TQN remembrance by using the quality theory from Daming and the developmental theory from Huvinggurst. This study uses a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation studies as well as validation of research results. The results of the study indicate that in general the implementation of TQN remembrance in fostering student piety carried out in general education providers, namely SMA and religion-based education providers, namely MA (Madrasah Aliyah) has been carried out objectively and measurably. In this case, basically the principles of TQN remembrance development starting from planning, implementation, evaluation and follow-up in the field have been carried out in accordance with management theories, concepts and principles, although in its implementation there are several obstacles that hinder optimal management due to the incompatibility between reality and the demands of the institution's wishes in this case as a determinant of internal policy makers. directed and appropriate. This is done so that the desired quality can be achieved and meet applicable standards. In addition, in the planning stage of this strategy, it is also necessary to analyze the needs of consumers or customers in order to help increase customer satisfaction with the products and services produced.